2016
DOI: 10.3892/ol.2016.5220
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chromosomal regional maintenance protein-1 may be associated with subcellular survivin expression in human gastric and colorectal carcinoma

Abstract: Abstract. Survivin, a member of the inhibitor of apoptosis protein family, is a potential prognostic marker and molecular target for anticancer therapies. Chromosomal regional maintenance protein-1 (CRM-1) mediates the nuclear export of proteins such as survivin. The aims of the present study were to compare the expression and subcellular localization of CRM-1 in human gastric and colorectal carcinomas and to assess the association between CRM-1 and survivin expression in these tumor types. The nuclear and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this study we identified a high tendency of XPO1 overexpression towards the moderate/poorly differentiated tumors as well as increase of XPO1 overexpression frequency in advance tumor stages III-IV with significant difference. Although Shintani et al, (2016) studied the XPO1 expression in CRC tissue samples, they did not find such association in CRC tissues which may attribute to the large differences in the sample sizes in each of well and poorly differentiated tumor groups; others were found such association in other types of cancers such as ovarian cancer (Noske et al, 2008), glioma (Shen et al, 2009) and the XPO1 expression was increased from well to poorly differentiated breast tumors (Yue et al, 2018). Additionally, we noted that the poorly differentiated tumors were significantly increased numbers of metastatic lymph nodes, which goes in line with a cohort study results of 124,180 CRC patients by Ricciardi et al, (2006) who concluded that the poorly differentiated tumors were much more likely to be with lymph node positive than well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we identified a high tendency of XPO1 overexpression towards the moderate/poorly differentiated tumors as well as increase of XPO1 overexpression frequency in advance tumor stages III-IV with significant difference. Although Shintani et al, (2016) studied the XPO1 expression in CRC tissue samples, they did not find such association in CRC tissues which may attribute to the large differences in the sample sizes in each of well and poorly differentiated tumor groups; others were found such association in other types of cancers such as ovarian cancer (Noske et al, 2008), glioma (Shen et al, 2009) and the XPO1 expression was increased from well to poorly differentiated breast tumors (Yue et al, 2018). Additionally, we noted that the poorly differentiated tumors were significantly increased numbers of metastatic lymph nodes, which goes in line with a cohort study results of 124,180 CRC patients by Ricciardi et al, (2006) who concluded that the poorly differentiated tumors were much more likely to be with lymph node positive than well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The XPO1, also known as chromosomal maintenance 1 (CRM1), is a nuclear export chaperone, mediates the nuclear export of several proteins which are essential for growth regulation and tumor suppression such as p53, leading to cytoplasmic degradation (9). Overexpression of XPO1 is identified in CRC (10) and the accumulated evidence suggests that both p53 and XPO1 are working in reciprocal manner, while the XPO1 gene has a binding site for p53 and its transcription activity may be repressed by p53, the increased activity of XPO1 can cause the p53 mislocalization and dysfunction in cancers (11,12). From the above indications and because of individual marker expression has a limited prognostic value, we aimed to evaluate the association between the expression of p53 and clinicopathological features in CRC Yemeni patents, which is still unknown, and tried to explore the ambiguous relationship between the coexpression of p53 and XPO1 in CRC tissue samples in relation to histopathological features.…”
Section: Introductionmentioning
confidence: 99%
“…The survivin protein inhibits caspase activation, thereby leading to negative regulation of apoptosis. This has been demonstrated by the disruption of survivin induction pathways leading to an increase in apoptosis and a decrease in tumor growth (50,51). Survivin inhibits both Bax and Fas-induced apoptotic pathways and blocks apoptosis by directly inhibiting caspases (52).…”
Section: Discussionmentioning
confidence: 99%